Exploring the aging effect of the anticancer drugs doxorubicin and mitoxantrone on cardiac mitochondrial proteome using a murine model - Brandão, Sofia Reis (2021)
Current cancer therapies are successfully increasing the lifespan of cancer patients. Nevertheless, cardiotoxicity is a serious chemotherapy-induced adverse side effect. Doxorubicin (DOX) and mitoxantrone (MTX) are cardiotoxic anticancer agents, whose toxicological mechanisms are still to be identified. This study focused on DOX and MTX's cardiac mitochondrial damage and their molecular mechanisms. As a hypothesis, we also sought to compare the cardiac modulation caused by 9 mg/kg of DOX or 6 mg/kg of MTX in young adult mice (3 months old) with old control mice (aged control, 18-20 months old) to determine if DOX- and MTX-induced damage had common links with the aging process. Cardiac homogenates and enriched mitochondrial fractions were prepared from treated and control animals and analyzed by immunoblotting and enzymatic assays. Enriched mitochondrial fractions were also characterized by mass spectrometry-based proteomics. Data obtained showed a decrease in mitochondrial density in young adults treated with DOX or MTX and aged control, as assessed by citrate synthase (CS) activity. Furthermore, aged control had increased expression of the peroxisome proliferator-activated receptor γ coactivator 1 α (PGC1α) and manganese superoxide dismutase (MnSOD). Regarding the enriched mitochondrial fractions, DOX and MTX led to downregulation of proteins related to oxidative phosphorylation, fatty acid oxidation, amino acid metabolic process, and tricarboxylic acid cycle. MTX had a greater impact on malate dehydrogenase (MDH2) and pyruvate dehydrogenase E1 component subunit α (PDHA1). No significant proteomic changes were observed in the enriched mitochondrial fractions of aged control when compared to young control. To conclude, DOX and MTX promoted changes in several mitochondrial-related proteins in young adult mice, but none resembling the aged phenotype.